Solution Mathematics SP 2_49268739_2024_12_31_07_50
Solution Mathematics SP 2_49268739_2024_12_31_07_50
Solution Mathematics SP 2_49268739_2024_12_31_07_50
MATHEMATICS SP 2
Class 12 - Mathematics
Section A
1. (a) 40
Explanation:
40
2.
∣ x1 y1 1∣
∣ ∣
(d) ∣ x2 y2 1 ∣ = ±2A
∣ ∣
∣ x3 y3 1∣
Explanation:
∣ x1 y 1∣
1
∣ ∣
∣ x2 y2 1 ∣ = ±2A
∣ ∣
∣ x3 y3 1∣
y
Explanation:
em
A= 1
2
[x1 (y2- y3) - x2 (y1-y3) + x3( y1-y2)]
2A = [x1 (y2- y3) - x2 (y1-y3) + x3( y1-y2)]
3.
d
ca
(d) 36
Explanation:
36
dA
4.
(b) 1
det(A)
Explanation:
Ar
So, ∣∣A −1
∣
∣ = ∣∣ 1
Adj(A)
∣
∣
|A|
= 1
n
| Adj(A)|
|A|
1 n−1 1
= n |A| =
1
|A| |A|
1
=
1
|A|
5.
8√3
(c) cos −1
(
15
)
Explanation:
→ −−−−−−−− –
Let a⃗ = ^
ı − ^
^
ȷ − 2k and b = 3^
ı − 5^
^
ȷ − 4k and |a⃗| = √1 + 1 + 2
2
= √6
→ −− −−−−−−−−
2 2 2 –
| b | = √3 + 5 + 4 = 5√2
⃗
a⃗⋅ b
cos α =
⃗
| a⃗|×| b|
^ ^ ^
(3 ^
ı −5^
ȷ −4k)⋅( i − ^
ȷ −2k)
⇒cos α =
5√2× √6
1 / 15
3+5+8
⇒ cos α =
5√12
8√3
⇒ cos α =
15
6. (a) x3 + y3 = 12x + C
Explanation:
We have ,
dy
2 2
x + y = 4
dx
dy
2 2
y = 4 − x
dx
2 2
y dy = (4 − x ) dx
2 2
⇒ ∫ y dy = ∫ (4 − x ) dx
3 3
y
⇒
3
= 4x −
x
3
+C
⇒ y3 + 12x - x3 + C
⇒ x3 + y3 = 12x + C
7.
(b) 5 corner points including (7, 7) and (3, 3)
y
Explanation:
dem
ca
dA
vin
On plotting the constraints x = 3, x = 9, x = y and x + y = 14, we get the following graph. From the graph given below it, clear
that feasible region is ABCDEA, including corner points A(9, 0), B(3, 0), C(3, 3), D(7, 7) and E(9, 5).
Thus feasible region has 5 corner points including (7, 7) and (3, 3).
Ar
8.
−2
(d) 3
Explanation:
⃗
a⃗⋅ b
|b|
=0
a⃗ ⋅ b
⃗
=0
^ ^
^ ^ ^
( i − 2 j + 3k) ⋅ (2 + λ ) i k =0
2 × 1 + 3λ = 0
2 + 3λ = 0
3λ = -2
−2
λ =
3
2
sin x−cos x
I = ∫ dx
1+sin x cos x
0
2 / 15
equals zero. By symmetry, I + I ′
= 0 , where I is the integral with sin and cos swapped. Thus, the answer is zero.
′
10.
(c) 2
Explanation:
2
11.
(c) 41
Explanation:
Corner Point Z = 0.7x + y
(0, 0) 0.7 × 0 + 0 = 0
(40, 0) 0.7 × 40 + 0 = 28
y
12. (a) aa + cc =– 1′ ′
em
Explanation:
x = ay + b, z = cy + d
x−b z−d
L1 : a
=y= c
x = a y + b ,z= c y + d
L2 :
x−b
′
=y=
′
z−d
′
′
′
d
ca
′ ′
a c
2
π
cos 2
=0
dA
′
aa + cc ±– 1
′
=0
′ ′
aa + cc =– 1
13.
(b) 1, -7, 1
Explanation:
vin
∣3 ∣
Ar
2
M22 = ∣ ∣ = -3 - 4 = -7
∣2 −1 ∣
∣3 −1 ∣
M33 = ∣ ∣ = -3 + 4 = 1
∣4 −1 ∣
14.
(d) 1
Explanation:
1
15.
4
(c) xy = x
4
+ C
Explanation:
3 / 15
dy y
2
+ = x
dx x
1 2
Here P = ,Q = x
x
1
∫ P .dx ∫ .dx
⇒ I. F . = e = e x
log|x|
= e = x
2
⇒ y. x = ∫ x. x dx ⇒ xy
4
x
= + C
4
16.
−−
5
(b) √ 21
Explanation:
−−
5
√
21
17.
(d) f(x) is not continuous at x = 1 and x = 2
y
Explanation:
Since, 0 ≤ x < 1 ⇒ -1 ≤ x - 1 < 0 ⇒ [x - 1] = -1
em
1 ≤ x < 2 ⇒ 0 ≤ x - 1 < 1 ⇒ [x - 1] = 0
And 2 ≤ x < 3 ⇒ [x] = 2
Therefore, given function may be written as
−x, 0 ≤ x < 1
f(x) = ⎨
⎧
⎪
⎩
⎪
0, 1 ≤ x < 2
d
ca
2(x − 1), 2 ≤ x < 3
From the graph it is obvious that f(x) is not continuous at x = 1 and 2, and thus not differentiable.
dA
vin
Ar
18. (a) 3, 1, - 2
Explanation:
We have,
x - y + z - 5 = 0 = x - 3y - 6
⇒ x - 3y - 6 = 0
&, x - y + z - 5 = 0
⇒ x = 3y + 6 ....(i)
x - y + z - 5 = 0 ...(ii)
From (i) and (ii)
We get, 3y + 6 - y + z - 5 = 0
⇒ 2y + z + 1 = 0
−z−1
⇒ y =
2
x−6
y= 3
[from (i)]
4 / 15
x−6 −z−1
∴ = y =
3 2
Hence, the direction ratios of the given line are proportional to 3, 1, -2.
19.
(b) Both A and R are true but R is not the correct explanation of A.
Explanation:
x −x
e +e
Assertion Let f(x) = 2
x −x
e −e
⇒ f'(x) = 2
=
1
2
(e
x
−
1
e
x
)
2x
e −1
= 1
2
(
e
x
) ...(i)
Now, for x ≥ 0, we have
2x ≥ 0 ⇒ e2x ≥ e0 [∵ ex is an increasing function]
⇒ e2x ≥ 1
Also, for x ≥ 0
⇒ ex ≥ 1
y
∴ From Eq. (i), we have
2x
e −1
f'(x) = 1
( ) ≥ 0
em
2 ex
So, all elements of B has a domain element on A or we can say elements 1 and 8 & 5 and 9 have some range 4 & 6,
vin
respectively.
Therefore, f : A → B is a surjective function not one to one function.
Also, for a bijective function, f must be both one to one onto.
Ar
Section B
21. We have, cos-1( = cos-1(cos
1 π
) )
2 3
= π
3
[∵
π
3
∈ [0, π]]
Also sin-1(− 1
2
) = sin-1 (-sin π
6
)
= sin-1 (sin(− π
6
))
=- π
6
[∵ −
π
6
∈ [−
π
2
,
π
2
]]
∴ cos-1( 1
2
) - 2sin-1(− 1
2
) = π
3
- 2(− π
6
)
= π
3
+ π
3
= 2π
OR
−π
tan
−1
(tan
3π
π
) ≠
3π
4
as 3π
4
∉ (
2
,
π
2
)
−1 3π −1 π
∵ tan (tan ) = tan [tan(π − )]
4 4
−1 π
= tan [− tan( )]
4
π
= −
4
5 / 15
22. Given: f (x) = cos(2x + π
4
)
′ π
f (x) = −2 sin(2x + )
4
Now,
3π 7π
x ∈ ( , )
8 8
3π 7π
⇒ < x <
8 8
3π 7π
⇒ < 2x <
4 4
π 3π π 7π π
⇒ + < 2x + < +
4 4 4 4 4
π
⇒ π < 2x + < 2π
4
π
⇒ sin(2x + )< 0
4
π
⇒ −2 sin(2x + )> 0
4
′
⇒ f (x) > 0
8
,
7π
8
)
4
at x = π
6
and min. value is 1
2
at x = π
2
sin x = 0
2 cos x = sin x
π π
=
6 3
y
f (
π
2
) = sin
π
2
+
1
2
cos
π
2
= 1
π π π √3
=
em
1 1
f ( ) = sin + cos +
6 6 2 6 2 4
π π 1 π √3 1
f (
3
) = sin
3
+
2
cos
3
= 2
+
4
OR
Given, f(x) = x3 - 3x2 + 6x -100 d
Therefore, on differentiating both sides w.r.t. x, we get,
ca
f'(x) = 3x2 - 6x + 6
= 3x2 - 6x + 3 + 3
dA
= 3 (x2 - 2x + 1) + 3
= 3 (x -1)2 + 3 >0
∴ f' (x) > 0
2
x +x
24. Let I = ∫ dx
x3 − x2 +x−1
2
x +x Bx+C
Now let 2
= A
+
(x−1)(x +1) x−1 x2 +1
Getting A = 1, B = 0, C = 1
Ar
Therefore, I = ∫ dx +∫
x−1
1
2
1
dx
x +1
= log |x − 1| +tan-1 x + C
25. Given, C(x) = 0.005x3 - 0.02x2 + 30x + 50
On differentiating both sides w.r.t. x, we get
dC 2
= 0.005 (3x ) − 0.02(2x) + 30
dx
= 0.015x2 - 0.04x + 30
On putting x = 300, we get
dC 2
= 0.015(300) − 0.04(300) + 30
dx
= 1350 - 12 + 30 = 1368
Therefore,the marginal cost of food for 300 students is Rs 1368.
By providing free mid-day meals to the students of primary classes, care and concern is shown towards their health and nutritional
status.
Section C
26. In order to solve as a limit of sum we have.
b b−a
∫
a
f (x)dx = lim h [f(a) + f(a + h) + f(a + 2h) + ..... + f(a + (n - 1)h] Where h = n
h→0
x2 +
3−1
Here, a = 1, b = 3, f(x) = x and h= n
=
2
n
3
2
∴ I = ∫ (x + x) dx
1
6 / 15
⇒ I = lim h [f(1) + f(1 + h) + f(1 + 2h) + f(1 + 3h) + ...... + f(1 + (n - 1)h]]
h→0
⇒ I = lim h [{12 + 1} + {(1 + h)2 + (1 + h)} + {(1 + 2h)2 + (1 + 2h)} + ....... + {(1 + (n - 1)h)2 + (1 + (n - 1)h)}]
h→0
⇒ I = lim h [{n + 2h(1 + 2 + 3 + ...... + (n - 1)) + h2 (12 + 22 + ...... + (n - 1)2)} + {n + h(1 + 2 + 3 + ..... + (n - 1)}]
h→0
n(n−1) n(n−1)(2n−1)
2
⇒ I = lim h [2n + 3h × + h × ]
2 6
h→0
2 6 n(n−1) 4 n(n−1)(2n−1) 2
⇒ I = lim [2n + × + × ] [∵ h = ]
n n 2 2 6 n
n→∞ n
n−1 4 (n−1)(2n−1)
⇒ I = lim [4 + 6 ( ) + ]
n 3 2
n→∞ n
1 4 1 1
⇒ I = lim [4 + 6 (1 − )+ (1 − ) (2 − )]
n 3 n n
n→∞
4 8 38
⇒ I = 4 + 6(1 − 0) + (1 − 0)(2 − 0) = 4 + 6 + =
3 3 3
y
= =
6 3 6 3
em
A 1 A 3
P( )= , P( )=
E1 2 E2 8
E1 P ( E1 )P (A/E1 )
8
P( )= =
A P ( E1 )P (A/E1 )+P ( E2 )P (A/E2 ) 11
sin 4x−4
28. According to the question, I = ∫ e
x
(
1−cos 4x
) dx ad
x 2 sin 2x cos 2x−4 ∵ sin 2x = 2 sin x cos x and
= ∫ e ( ) dx [ ]
2 2
2 sin 2x
cos 2x = 1 − 2 sin x
Ac
x 2 sin 2x cos 2x 4
= ∫ e ( − ) dx
2 2
2 sin 2x 2 sin 2x
x 2
= ∫ e (cot 2x − 2 cosec 2x) dx
We know that,
x ′ x
∫ e [f (x) + f (x)] dx = e f (x) + C
′ 2
⇒ f (x) = −2cosec 2x
vin
x
∴ I = e cot2x + C
OR
4
4 (x −1)+2
1 x +1 1
Given, I = ∫ 0 2
dx ⇒ I = ∫
0 2
dx
x +1 x +1
2 2
Ar
(x −1)(x +1)+2
1
= ∫ dx
0 2
x +1
[∵ (a 2 2
− b ) = (a − b)(a + b)
2 2
1 (x −1)(x +1)
2
= ∫ [ + ] dx
0 2 2
x +1 x +1
1 2 2
⇒ I = ∫ [x − 1 + ] dx
0 2
x +1
3 1
x −1
⇒ I = [ − x + 2 tan x]
3
0
1 −1 2 π 3π−4
∴ I = − 1 + 2 tan 1 − 0 = − + 2 × =
3 3 4 6
dx
(1 + x2) = x + 2 tan-1 x
dy
⇒
dx
x 2 −1
⇒ dy = { + ( ) tan x} dx
1+x2 1+x2
1 2x 2 −1
⇒ dy = { × + ( ) tan x} dx
2 2 2
1+x 1+x
1 2x 1 −1
⇒ y = ∫ dx + 2 ∫ [ tan x] dx
2 2 2
1+x 1+x
7 / 15
1 2 1 −1
⇒ y = log∣
∣1 + x ∣
∣ + 2∫ [ tan x] dx
2 2
1+x
Putting tan-1 x = t
1
⇒ dx = dt
1+x2
1 2
∴ y = log∣
∣1 + x ∣
∣ + 2 ∫ tdt
2
= 1
2
log |1 + x2| + t2 + C
log |1 + x2| + (tan-1 x)2 + C
1
= 2
Hence, y = 1
2
log |1 + x2| + (tan-1 x)2 + C is the solution to the given differential equation.
OR
dy
According to the question , dx
− y = cos x
dy
This is a linear differential equation of the form dx
+ Py = Q ,
Where P = −1 and Q = cosx
we know that ,
∫ Pdx ∫ (−1)dx −x
IF = e = e = e
y
⇒ ye
−x
= ∫ e
−x
cos xdx + C ...(i)
Now, ∫ −x −x −x
em
e cos xdx = e sin x + ∫ e sin xdx
I II I II
−x −x
⇒ 2∫ e cos xdx = e (sin x − cos x) ad
−x 1 −x
⇒ ∫ e cos xdx = e (sin x − cos x)
2
On putting C = 3
in Eq. (ii), we get
d
−x 1 −x 3
y ⋅ e = e (sin x − cos x) +
2 2
vin
1 3 x
⇒ y = (sin x − cos x) + e
2 2
follows:
3x + 4 y = 24, 8x + 6 y = 48,x = 5, y = 6, x = 0 and y = 0
The line 3x + 4 y = 24 meets the coordinate axis at A(8,0) and B(0,6). Join these points to obtain the line 3x + 4 y = 24 Clearly, (0,
0) satisfies the inequation 3x + 4 y ≤ 24.50, the region in xy-plane that contains the origin represents the solution set of the given
equation.
The line 8 x+ 6 y = 48 meets the coordinate axis at C(6,0) and D(0,8). Join these points to obtain line 8 x+ 6 y = 48. Clearly, (0,0)
satisfies the inequation 8x + 6y ≤ 48. So, the region in XY-plane that contains the origin represents the solution set of the given
equation.
x = 5 is the line passing through x = 5 parallel to the Y-axis.
y = 6 is the line passing through y = 6 parallel to the X-axis.
The region represented by non negative restrictions ,x ≥ 0 and y ≥ 0 :
since every point in the first quadrant satisfies these inequations. So, the first quadrant is the region represented by the
inequations.
These lines are drawn using a suitable scale.
8 / 15
The corner points of the feasible region are O(0,0), G(5,0), F (5, 4
3
) , E( 24
7
,
24
7
) and B(0, 6), The values of objective function Z
at these corner are as follows.
Corner point Z = 4x + 3y
O(0, 0) 4×0+3×0=0
G(5, 0) 4 × 5 + 3 × 0 = 20
4 4
F (5, ) 4 × 5 + 3 × = 24
3 3
y
24 24 24 24 196
E( , ) 4 × + 3 = = 24
7 7 7 7 7
em
24 24 196
B(0, 6) 4 ×
7
+ 3
7
=
7
= 24
We see that the maximum value of the objective function z is 24 which is at F (5, 4
3
) and E ( 24
7
,
24
7
)
d dy d d
⇒ y log cos x + log cos x = x log cos y + log cos y x
dx dx dx dx
1 d dy 1 d
⇒ y cos x + log cos x = x cos y + log cos y.1
cos x dx dx cos y dx
1 dy 1 dy
⇒ y (− sin x) + log cos x = x (− sin y ) + log cos y
cos x dx cos y dx
dy dy
⇒ −y tan x + log cos x = −x tan y. + log cos y
dx dx
dy dy
⇒ x tan y
dx
+ log cos x.
dx
= y tan x + log cos y
dy
⇒
dx
(x tan y + log cos x) = y tan x + log cos y
dy y tan x+log cos y
⇒ =
dx x tan y+log cos x
Section D
32. According to the question ,
Given parabola is y2 = x......(i)
vertex of parabola is ( 0, 0)
axis of parabola lies along X-axis.
Given equation of line is x + y = 2.......(ii)
For, x + y = 2
x 2 0
9 / 15
y 0 2
So, line passes through the points (2, 0) and (0, 2).
Now, let us sketch the graph of given curve and line as shown below:
2
⇒ y + y − 2 = 0
2
⇒ y + 2y − y − 2 = 0
⇒ y(y + 2) − 1(y + 2) = 0
y
⇒ (y − 1)(y + 2) = 0
y = 1 or -2
em
∴
When y = 1, then x = 2 - y = 1
When y = -2, then x = 2 - y = 2 - (- 2) = 4
So, points of intersection are (1, 1) and (4, - 2). ad
1
Now, required area = ∫ −2
[ x(line) − x
(parabola) ] dy
1 2
= ∫ (2 − y − y ) dy
−2
2 3 1
Ac
y y
= [2y − − ]
2 3
−2
1 1 8
= (2 − − ) − (−4 − 2 + )
2 3 3
5 8
= 2 − + 6 −
6 3
5 8
= 8 − −
d
6 3
48−5−16
=
6
vin
48−21
=
6
27
=
6
=
9
2
sq units.
33. i. Let (a1 b1) and (a2, b2) ∈ A × B such that
Ar
10 / 15
R = {(a,b) = |a.b| is divisible by 2.
where a, b ∈ A = {1, 2, 3, 4, 5}
reflexivty
For any a∈A,|a−a|=0 Which is divisible by 2.
∴ (a, a) ∈ r for all a ∈ A
So ,R is Reflexive
Symmetric :
Let (a, b) ∈ R for all a, b ∈ R
|a−b| is divisible by 2
|b−a| is divisible by 2
(a, b) ∈ r ⇒ (b, a) ∈ R
So, R is symmetirc .
Transitive :
Let (a, b) ∈ R and (b, c) ∈ R then
(a, b) ∈ R and (b, c) ∈ R
|a−b| is divisible by 2
|b−c| is divisible by 2
y
Two cases :
Case 1:
em
When b is even
(a, b) ∈ R and (b, c) ∈ R
|a−c| is divisible by 2
|b−c| is divisible by 2
|a−c| is divisible by 2
ad
∴ (a, c) ∈ R
Case 2:
Ac
When b is odd
(a, b) ∈ R and (b, c) ∈ R
|a−c| is divisible by 2
|b−c| is divisible by 2
d
|a−c| is divisible by 2
vin
x
1
y
1
z
Ar
2u + 3v + 10w = 4; 4u − 6v + 5w = 1; 6u + 9v − 20w = 2
2 3 10 x 4
⎡ ⎤⎡ ⎤ ⎡ ⎤
2 3 10 x 4
⎡ ⎤ ⎡ ⎤ ⎡ ⎤
Here, A = ⎢ 4 −6 5 ⎥,X⎢ v ⎥ and B = ⎢ 1 ⎥
⎣ ⎦ ⎣ ⎦ ⎣ ⎦
6 9 −20 z 2
∣2 3 10 ∣
∣ ∣
∴ |A| = 4 −6 5
∣ ∣
∣6 9 −20 ∣
11 / 15
75 150 75
⎡ ⎤
adj.A 1
And A −1
=
|A|
=
1200
⎢ 110 −100 30 ⎥
⎣ ⎦
72 0 −24
600
⎡ ⎤
1
= ⎢ 400 ⎥
1200
⎣ ⎦
240
1
⎡ 2 ⎤
⎢ 1 ⎥
= ⎢ ⎥
⎢ 3 ⎥
1
⎣ ⎦
5
1 1 1
∴ u = ,v = ,w =
2 3 5
y
1 1 1
⇒ x = = 2, y = = 3, z = = 5
u v w
em
3 5 −2
a b c
= =
(−2)(4)−(3)(1) (2)(1)−(3)(4) (3)(3)−(−2)(2)
a b c
= =
−8−3 2−12 9+4
a b c
= =
−11 −10 13
Let z = 0 so
3x – 2y = – 5 …… (i)
2x + 3y = 4 …… (ii)
Solving (i) and (ii) by eliminations method,
6 x - 4 y = -10
±6x ± 9y = ±12
– 13y = – 22
22
y =
13
12 / 15
7 22
x+ y−
13 13 z−0
= =
−11 −10 13
^ ^ ^ ⃗ ^ ^ ^
a⃗2 = 2 i + j − k, b2 = 3 i − 5 j + 2k
^ ^
a⃗2 − a⃗1 = i − k
∣^ ^ ^∣
i j k
∣ ∣
⃗ ⃗
b1 × b2 = ∣2 −1 1∣
∣ ∣
∣3 −5 2∣
^ ^ ^
= i (−2 + 5) − j (4 − 3) + k(−10 + 3)
y
^ ^ ^
= 3 i − j − 7k
∣ ⃗ ⃗ ∣ −−−−−−− − −−
b × b2 = √9 + 1 + 49 = √59
em
∣ 1 ∣
Also, (b ⃗ 1
⃗ ^ ^ ^ ^ ^
× b2 ). (a⃗2 − a⃗1 ) = (3 i − j − 7k)( i − k) = 3 + 7 + 0 = 10
⃗ ⃗
∣ ( b1 × b2 ).( a⃗2 − a⃗1 ) ∣ 10
d = ∣ ∣ =
⃗ ⃗ √59
∣ | b1 × b2 | ∣
Section E
ad
Ac
36. i.
Here, P(E1) = 4
10
, P(E2) = 4
10
, P(E3) = 2
10
d
P (
E1
A
) = 45
100
,P( A
E2
) = 100
60
,P( A
E3
) = 35
100
vin
∴ P(A) = P(E1) ⋅ P( A
E1
) + P(E2) ⋅ P (
A
E2
) + P(E3) ⋅ P (
A
E3
)
4 45 4 60 2 35
= 10
×
100
+
10
×
100
+
10
×
100
180 240 70
= 1000
+
1000
+
100
490
= = 4.9
Ar
1000
E2
ii. Required probability = P ( )
A
A
P ( E2 )⋅P ( )
E
=
2
P (A)
4 60
×
= 10
490
100
1000
= 240
490
= 24
49
iii. Let,
E1 = Event for getting an even number on die and
E2 = Event that a spade card is selected
3
∴ P(E1) = 6
= 1
2
13 1
and P(E2) = 52
=
4
2
, 1
4
= 1
OR
P(A) + P(B) - P(A and B) = P(A)
13 / 15
⇒ P(A) + P(B) - P(A ∩ B) = P(A)
⇒ P(B) - P(A ∩ B) = 0
⇒ P(A ∩ B) = P(B)
P (A∩ B)
∴ P(A|B) =
P (B)
P (B)
=
P (B)
=1
37. i. Resultant velocity from O to A
−−−−−−−−−−−−−−−−
2 2
= √(V ) + (V )
Plane wind
−−−−−−−−−− −
2 2
= √(120) + (50)
−−−−−−−−− −−
= √14400 + 2500
−−−−−
= √16900
= 130 m/s
V
wind
ii. tan θ = V
aeroplane
50
tan θ =
120
5
tan θ =
y
12
−1 5
θ = tan ( )
em
12
h
d
Let l ft be the length and h ft be the height of the tank. Since breadth is equal to 5 ft. (Given)
Two sides will be 5h sq. feet and two sides will be lh sq. feet. So, the total area of the sides is (10 h + 2lh)ft2
vin
Cost of the sides is ₹10 per sq. foot. So, the cost to build the sides is (10h + 2Ih) × 10 = ₹(100h + 20Ih)
Also, cost of base = (5 l) × 20 = ₹100 l
∴ Total cost of the tank in ₹ is given by c = 100 h + 20 lh + 100l
Ar
16 16
∴ c(h) = 100h + 20 ( h
) h + 100 (
h
)
1600
= 100h + 320 + h
1600
ii. C(h) = 100h + 320 + h
dC(h) 1600
= 100 −
dh 2
h
2
d C(h) −2
= −( ) 1600
2 3
dh h
at h = 4
2
d C(h)
2
= 50 > 0
dh
dh
⇒ 100 - 1600
2
=0
h
⇒ 100h2 = 1600 ⇒ h2 = 16 ⇒ h = ± 4
⇒ h = 4 [∵ height can not be negative]
OR
14 / 15
Minimum cost of tank is given by
c(4) = 400 + 320 +1600
y
em
ad
d Ac
vin
Ar
15 / 15